Justifying Christianity in the Islamic middle ages: the apologetic theology of ʿAbdīshōʿ bar Brīkhā (d. 1318) - Rassi, S (2015)
The subject of this thesis is the theology of the late 13th- early 14th century churchman 'Abdīshō' bar Brīkhā. Better known by modern scholars for his poetry and canon law, he is far less recognised as a religious controversialist who composed works in Arabic as well as Syriac to answer Muslim criticisms. My overall argument contends that 'Abdīshō''s hitherto neglected theological works are critical to our understanding of how anti-Muslim apologetics had by his time become central to his Church's articulation of a distinct Christian identity in a largely non-Christian environment. 'Abdīshō' wrote his apologetic theology at a time when Christians experienced increasing hardship under the rule of the Mongol Ilkhans, who had officially converted to Islam in 1295. While the gradual hardening of attitudes towards Christians may well have informed 'Abdīshō''s defensive stance, this thesis also demonstrates that his theology is built on a genre of apologetics that emerged as early as the mid-8th century. Our author compiles and systematises earlier debates and authorities from this tradition while updating them for a current authorship. In doing so, he contributes to the formation of a theological canon that would remain authoritative for centuries to come. My analysis of 'Abdīshō''s oeuvre extends to three doctrinal themes: the Trinity, the Incarnation, and devotional practices (viz. the veneration of the Cross and the striking of the church clapper). I situate his discussion of these topics in a period when Syriac Christian scholarship was marked by a familiarity with Arabo-Islamic theological and philosophical models. While our author does not engage with these models as closely as his better-known Syriac Christian contemporary Bar Hebraeus (d. 1286), he nevertheless appeals to a literary and theological idiom common to both Muslims and Christians in order to convince his coreligionists of their faith’s reasonableness against centuries-long polemical attacks.